Long-term effects of acupuncture for chronic prostatitis/chronic pelvic pain syndrome: systematic review and single-arm meta-analyses - Qin, Zongshi; Wu, Jiani; Xu, Chang; Sang, Xiaopu; Li, Xiao; Huang, Guangrui; Liu, Zhishun (Annals of Translational Medicine; Vol 7, No 6 (March 28, 2019): Annals of Translational Medicine (Focus on “Clinical Evaluation of Evidence Based on Traditional Chinese Medicine”), 2018)
Background: Cumulative evidences indicate that acupuncture may ameliorate the symptoms of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). However, the long-lasting effects of acupuncture on CP/CPPS has not been fully evaluated. The objective of this study is to assess the sustained effects of acupuncture on CP/CPPS. Methods: We searched PubMed, EMBASE, and CENTRAL databases for studies on the use of acupuncture in patients with CP/CPPS. Studies with long-term follow-up periods were included. Single-arm meta-analyses were performed using random-effects model. The primary outcome was the response rate at the end of follow-up period; the secondary outcomes were changes of the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) scores at the end of follow-up, including total score and 3 sub-scores (pain, urinary, and quality of life). Results: Six studies with 310 patients were performed in data synthesis, among which four studies were randomized controlled trials (RCT) and two were case series studies. At the end of follow-up, the weighted “average” response rate was 68.4% (95% CI: 42.1% to 89.5%, n=226; I2=93.5%); the change of NIH-CPSI total score were −14.8 (95% CI: −17.0 to −12.6, n=310; I2=92.1%); the change of pain, urinary, and quality of life sub-scores were −6.0 (95% CI: −6.9 to −5.2, n=266; I2=83.6%), −2.6 (95% CI: −3.2 to −2.0, n=266; I2=87.9%), and −4.4 (95% CI: −6.2 to −2.6, n=266; I2=98.7%), respectively. The source of heterogeneity could not be identified owing to insufficient studies. Conclusions: Acupuncture may have clinically long-lasting benefits for CP/CPPS. However, current evidence is limited owing to insufficient data and significant heterogeneity. Further studies with larger sample size and long-term follow-up periods are warranted.